SEASONAL TESTICULAR HISTOLOGY AND REPRODUCTIVE CYCLE OF THE RAINBOW LIZARD, Agama agama agama , L, (AGAMIDAE, REPTILIA) IN ILE-IFE, SOUTH WESTERN NIGERIA - EJERE, Vincent Chikwendu; ADEGOKE, Joseph Adeleke (Animal Research International, 2023)
Animal Research International ,NO .2,VOL .3,pg . 393 – 398